ALIENATION, DIASPORA, AND GLOBALIZATION: REFLECTIONS IN CONTEMPORARY FICTION OF ANURAG MATHUR, ARUNDHATI ROY, AND MANJU KAPUR - Sanap, Sarala Kisan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In an era marked by unprecedented connectivity, the themes of alienation, diaspora, and globalization have become central to contemporary literature, especially in the works of Indian authors like Anurag Mathur, Arundhati Roy, and Manju Kapur. Their novels resonate with readers worldwide, portraying the impact of globalization on individual identities, familial ties, and societal norms. This paper explores how these authors portray the psychological, social, and cultural repercussions of globalization, displacement, and alienation, particularly through the lens of their protagonists. Focusing on Mathur’s The Inscrutable Americans, Roy’s The God of Small Things, and Kapur’s Difficult Daughters and Home, this paper critically examines how these narratives offer nuanced perspectives on the Indian diaspora, the sense of alienation in a postcolonial context, and the impact of modernity on traditional values. Through an exploration of their unique approaches, this study sheds light on how these works reflect the challenges and transformations of contemporary India within a globalized world.